IMPACT OF ISLAMIC VALUE TO SCHOOL MANAGEMENT: CASE STUDY OF EARLY CHILDHOOD EDUCATION PROGRAMS - Nurus Shalihin; Firdaus Firdaus; M. Yusuf (Ta'dib, 2021)
School management is influenced by the norms, values and rules that they make as a platform. This article aims to analyze the influence of moral values platform (Islamic value) toward school management of early childhood education in Indonesia. With case study approach at 6 Islamic Kindergarten (TK IT) in Padang, data were collected through in-depth interviews with teachers and foundation leaders. FGDs were also conducted with the school principal in order to do the data enrichment and triangulation. Data were analized through data reduction, data display and data ferivication. The study results show three types of Integrated Islamic Kindergartens (TK IT) in Indonesia with different Islamic platforms, namely TK IT affiliated with JSIT, TK IT affiliated with ASESI and TK IT non-afiliated. These three type of integrated Islamic schools have Islamic platform on developed their schools. The difference of platform influenced the management of Integrated Islamic Kindergartens (TK IT) which includes design of school target, academic standard policies of school, and human resource management. Thus, the authors argue that the Islamic values on the school platform determine the school management.